The avifauna of the reserve of national importance "Luchkivskiy" - Шупова, Т. В.; Чаплигіна, А. Б. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
Diversity of avifauna in the reserve of national importance "Luchkivskiy", distribution of birds in its biotopes and changes occurred in the communities of birds since 1996 were analyzed. In the nesting period there have been observed 112 species of birds, 88 of which nest. The average density of nesting birds is 1.2±0.17 pairs/km2. Dendrofils (46 species) dominate in ecological structure. Nemoral (17), ancient nemoral (12) and forest-steppe (12) species dominate in the landscape genetic structure. The most numerous are Fringilla coelebs (Pi=0.09), Merops apiaster (Pi=0.06), Turdus merula (Pi=0.05). Species diversity of birds in steppe habitat is low, in meadow is the highest. The communities of nesting birds in steppe and forest habitats are similar: 38 common species, Jaccard index is 0.6, Sorensen – 0.8. Recreational load in the reserve is mild. This explains the abundance of birds nesting on the ground (27.8%) and in shrub layer (19.3%).